Pengaruh Canva terhadap Hasil Belajar Siswa dalam Pembelajaran IPAS Kelas V SDN Gugus XII Kota Bengkulu - Aditama, Shanka; Noperman, Feri (Universitas Bengkulu, 2026)
This research aims to explore the impact of Canva application media on the learning achievements of fifth-grade IPAS students at SDN Gugus XII, Bengkulu City. It employs a quantitative approach using a quasi-experimental method, specifically adopting the Matching Only Pretest-Posttest Control Group Design. The study population comprises all fifth-grade students from SDN Gugus XII, Bengkulu City. The sample includes Class VA from SDN 60 Bengkulu City as the experimental group and Class V from SDN 81 Bengkulu City as the control group. Data collection was carried out through pretest and posttest assessments using multiple-choice questions. The data were then analyzed using descriptive statistics and inferential techniques, namely the t-test. The analysis indicates no significant difference in posttest scores between the experimental and control groups. This is demonstrated by the t-value (-1.252) being greater than the t-table value (2.110), or a Sig. (2-tailed) result of 0.219 being lower than 0.05, leading to acceptance of the null hypothesis (H0) and rejection of the alternative hypothesis (Ha). Based on these findings, it can be concluded that the Canva application media does not significantly influence the learning outcomes of fifth-grade IPAS students at SDN Gugus XII in Bengkulu City.